Neural architecture search applying optimal stopping theory - Sheehan, Matthew; Yakimenko, Oleg (Frontiers in Artificial Intelligence, 2025)
Neural architecture search (NAS) exploration requires tremendous amounts of computational power to properly explore. This makes exploration of modern NAS search spaces impractical for researchers due to the infrastructure investments required and the time needed to effectively design, train, validate, and evaluate each architecture within the search space. Based on the fact that early-stopping random search algorithms are competitive against leading NAS methods, this paper explores how much of the search space should be explored by applying various forms of the famous decision-making riddle within optimal stopping theory: the Secretary Problem (SP). A total of 672 unique architectures, each trained and evaluated against the MNIST and CIFAR-10 datasets over 20,000 runs, producing 6,720 trained models confirm theoretically and empirically the need to randomly explore ~37% of the NAS search space until halting can occur for an acceptable discovered neural architecture. Additional extensions of the SP investigated include implementing a “good enough” and a “call back” feature; both further reduce exploration of the NAS search space to ~15 and 4%, respectively. Each of these investigations were further confirmed statistically upon NAS search space populations consisting of 100–3,500 neural architectures increasing in steps of 50, with each population size analyzed over 20,000 runs. The paper details how researchers should implement each of these variants, with caveats, to balance computational resource costs and the desire to conduct sufficient NAS practices in a reasonable timeframe.